2021
DOI: 10.21203/rs.3.rs-161008/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and correlates of psychological distress, unmet supportive care needs, and fear of cancer recurrence among haematological cancer patients during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic has had a disruptive effect on people with haematological cancers, who represent a high-risk population due to the nature of their disease and immunosuppressive treatments. We aimed to identify the psychological impacts of the COVID-19 pandemic on haematology patients and identify correlated factors to inform the development of appropriate supportive interventions.Methods 394 respondents volunteered their participation in response to a study advertisement distributed online thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…These results demonstrate the additional negative impact on people with cancer in low‐ and middle‐income countries (LMICs) in comparison to high‐income countries, where survey results were already alarming. For example, in Australia, 26% of respondents reported losing income and 29% indicated a worsening of financial concerns due to COVID‐19 21 . In a US‐based cancer patient survey, 46% of respondents reported experiencing some loss of income and nearly 48% were worried about the potential loss of health insurance 6 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrate the additional negative impact on people with cancer in low‐ and middle‐income countries (LMICs) in comparison to high‐income countries, where survey results were already alarming. For example, in Australia, 26% of respondents reported losing income and 29% indicated a worsening of financial concerns due to COVID‐19 21 . In a US‐based cancer patient survey, 46% of respondents reported experiencing some loss of income and nearly 48% were worried about the potential loss of health insurance 6 …”
Section: Resultsmentioning
confidence: 99%
“…For example, in Australia, 26% of respondents reported losing income and 29% indicated a worsening of financial concerns due to COVID-19. 21 In a US-based cancer patient survey, 46% of respondents reported experiencing some loss of income and nearly 48% were worried about the potential loss of health insurance. 6 In our study from Kenya, the economic impact of COVID-19 manifested negatively in participants' mental health.…”
Section: Participantsmentioning
confidence: 99%
“…Interviews were conducted by authors NZ and EY (who both hold PhDs in psycho‐oncology and are trained in qualitative research methods) between August and November 2020. A semi‐structured interview guide was used (see Table S1 ), which incorporated broad and open‐ended questions created by the authors based on a review of clinically relevant issues identified in the COVID‐19 literature and our previous research, 21 clinical experience, and consultation with haematology healthcare professionals. A panel of haematology healthcare professionals, psycho‐oncological academics, and haematology patients assessed the appropriateness of the interview guide, and all agreed that the questions were understandable and relevant.…”
Section: Methodsmentioning
confidence: 99%
“…Concerns about the impact of COVID-19 on cancer management were significantly associated with fear of cancer recurrence among responder in remission. 121 Other stressors were social distancing and limited social interactions induced by the pandemic. 122 Summary: management of patients with hematologic malignancy during the SARS-COV-2 pandemic For patients with HM, the current SARS-CoV-2 pandemic represents a particular challenge for at least 2 reasons.…”
Section: Psychologic Distressmentioning
confidence: 99%